ChemInform Abstract: Hypervalent Iodine Catalyzed Hofmann Rearrangement of Carboxamides Using Oxone as Terminal Oxidant. Issue 19 (18th April 2013) - Yoshimura, Akira; Middleton, Kyle R.; Luedtke, Matthew W.; Zhu, Chenjie; Zhdankin, Viktor V.
Abstract The reaction is proposed to proceed via electron‐deficient active species generated from hydroxy(phenyl)iodonium ion or hypervalent aminoiodane and (F3C)2CH—OH.